Sosialisasi dan Pelatihan Keamanan Pangan dan Proses Sertifikasi Halal Produk Makanan dan Minuman Olahan - Mamilianti, Wenny (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2024)
Purpose – This socialization and training activity aims to motivate business actors to continue to improve product quality and maintain food safety standards, as well as provide information, knowledge, and technical aspects of managing halal certificates so that Pucangsari village MSME products can develop further and improve the economy of the community and village. Design/methodology/approach – The method of implementing community service uses a survey, socialization, training, and evaluation approach. Socialization and training activities were carried out on July 14, 2024 at the Pucangsari village hall, after the socialization and training activities were continued with evaluation activities of the socialization and training activities. The evaluation results are used to improve the implementation of further training and the mentoring process after the program ends Findings – The result of this community service activity is that business actors in Pucangsari village gain knowledge and information on the importance of food safety and the halal certification process for food products, beverages and livestock slaughter results. Knowledge and management of halal certification has increased among business actors, this is indicated by their willingness to immediately take care of halal certification for their products Originality/value – Halal certificates are no longer foreign to the community, especially in the Pucangsari village community. However, only 3 UMKM have halal certificates for their products. This indicates that business actors' awareness and limited knowledge of halal certification is still low. Therefore, this community service activity is important to be carried out so that business actors in Puscangsari increase their awareness and knowledge of halal certification so that the number of products with halal certification will increase.